Propřírodně zaměřený učitel a jeho přístup k (environmentální) výchově - Létalová, Jana (Masaryk University Press, 2022)
Title in English: Pro-naturally focused teacher and his approach to (environmental) education The publication aims to cover the key factors which influenced the teacher´s biophile/pro-environmental orientation, and his approach to the education, and subsequently provide his life picture for which the term bioprofile is used. In order to fulfill the goal of the publication a qualitative approach was chosen. The group of respondents consisted of four teachers whose profiles corresponded with the set beforehand criteria. For data collecting and their analysis and interpretation the method of life history in combination with the narrative, phenomenological and hermeneutical approaches was used. The final bioprofile, which is mainly the result of the respondents´spontaneous narration, interlinks three related areas. These were detected within the process of the obtained data analysis and comparison. The submitted monography offers a more complex view of pro-environmentally oriented teacher. Exploring the life history of each respondent, enabled us not only to identify the essential factors which influenced the teacher´s biophile orientation, but also to understand deeper his personality and the way of his pedagogical thinking.